Influence of Nickel Loading and the Synthesis Method on the Efficiency of Ni/TiO2 Catalysts for Renewable Diesel Production - George Petropoulos; John Zafeiropoulos; Eleana Kordouli; Alexis Lycourghiotis; Christos Kordulis; Kyriakos Bourikas (Energies, 2023)
The efficiency of Ni/TiO2 catalysts for renewable diesel production was evaluated in the present study. Two series of catalysts were synthesized and characterized using various physicochemical techniques (N2 physisorption, XRD, SEM, XPS, H2-TPR, and NH3–TPD). In the first series of catalysts, successive dry impregnations (SDI) were used for depositing 10, 20, 30, 50, and 60 wt.% Ni. The yield towards renewable diesel is maximized over the catalyst with 50 wt.% Ni loading. Selecting this optimum loading, a second series of catalysts were synthesized via three additional preparation methods: wet impregnation (WI) and deposition–precipitation using either ammonia (DP-NH3) or urea (DP-Urea) as the precipitation agent. The catalysts’ efficiency in the production of green diesel is influenced by the preparation method following the order: DP-Urea > DP-NH3 > WI ≈ SDI. The metallic surface area and the balanced acidity mainly determine the performance of the catalysts.